Scleredema diabeticorum successfully treated with ultraviolet A1 phototherapy - Narumol Thumpimukvatana (2018)
Scleredema diabeticorum is an uncommon condition. It is one of the cutaneous manifestations in diabetes mellitus that mainly occurs in obese middle-aged men with insulin-resistant diabetes. This condition is generally recalcitrant to therapy. Various treatments have been tried with inconsistent results. Here, we describe two cases of scleredema diabeticorum with substantial clinical improvement from a course of medium dose (60 J/cm2) ultraviolet A1 radiation therapy. © 2010 Japanese Dermatological Association.